Utilization, preference and nutritional value of winter-green agricultural crops for goose food - Taylor, Warren Hassel (Virginia Tech, 1957)
Present data are insufficient to permit final recommendations as to the best winter-green crop for geese of the sight crops studied. Italian rye grass appears, however, to have very good possibilities because of its good production of forage, its utilization and apparent high preference by geese coupled with a low preference by deer. It is also a relatively inexpensive field crop. Ladino clover is good as a second year crop for both geese and deer besides being economical to plant and maintain, but should be planted early to permit satisfactory first year utilization. Oats, on the refuges on which this investigation was conducted, appears a poor choice because of its high preference by deer and low goose preference. There is a need for additional investigation to permit the accumulation of more conclusive data. Presently reported results reflect limitations which might be overcome with additional investigation. Master of Science